Solubility and dissolution kinetics of GaN in supercritical ammonia in presence of ammonoacidic and ammonobasic mineralizers - Schimmel, Saskia; Koch, Martina; Macher, Philipp; Kimmel, Anna-Carina; Steigerwald, Thomas; Alt, Nicolas; Schlücker, Eberhard; Wellmann, Peter (Journal of Crystal Growth, 2017)
Solubility and dissolution kinetics of GaN are investigated, as they represent essential parameters for ammonothermal crystal growth of GaN. In situ X-ray imaging is applied to monitor the dissolving crystal. Both ammonoacidic and ammonobasic conditions are investigated. Compared to NH4F, the dissolution is generally much slower using NaN3 mineralizer, leading to a much longer time needed to establish a saturated solution. The solubility of GaN at 540 °C and 260 MPa in supercritical ammonia with a molar concentration of NaN3 of 0.72 mmol/ml is determined to be 0.15 ± 0.01 mol%. This suggest a severe refinement of raw gravimetric literature data also for alkali metal based mineralizers, as we reported previously for ammonium halide mineralizers. The order of magnitude is in good agreement with refined gravimetric solubility data (Griffiths et al., 2016). The apparent discrepancy between the literature and this work regarding the temperature range in which retrograde solubility occurs is discussed. A possible reason for the occurrence of retrograde solubility at high temperatures is described. The paper is complemented by a section pointing out and partially quantifying potential, reactor-material-dependent sources of errors.
Keywords: Solubility; Solvents; Ammonothermal crystal growth; Growth from solutions; Solvothermal crystal growth; Gallium compounds